The Social World, Reexamined : A Conversation with Brian Epstein. - Burton, Howard (Toronto : Open Agenda Publishing, 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Brian Epstein, Associate Professor of Philosophy at Tufts University. Brian Epstein's career as a management consultant piqued his interest and his later research into the reasons why our current models of economics, politics and other areas of social science so often go terribly wrong. The conversation explores how we can dramatically improve our current economic and political models by reexamining our assumptions about the nature of the social world.This carefully-edited book includes an introduction, The Real Wo.
Intro -- A Note on the Text -- Introduction -- The Conversation -- I. Wondering About the World -- II. Empirical Influences -- III. Unquestioned Assumptions -- IV. Beyond Emergence -- V. Ontological Examinations -- VI. Better Models -- VII. Modelling Concerns -- VIII. Getting Specific -- IX. No, We Can't -- X. Responses and Reactions -- XI. The Value of Breadth -- XII. Learning Our Lessons? -- XIII. Applied Philosophy -- Continuing the Conversation
Description based upon print version of record.
JSTOR
Keywords: Epstein, Brian -- Interviews; Econometric models; Economics -- Mathematical models; Political science -- Mathematical models; Modèles économétriques.; Économie politique -- Modèles mathématiques.; Metaphysics; PHILOSOPHY; Social; Comparative Politics; POLITICAL SCIENCE; Econometric models; Economics -- Mathematical models; Political science -- Mathematical models; Interviews